HIV advice in the media: Implications for reinventing subjectivity - Nkomo, Nkululeko; Long, Carol (PINS-Psychology in Society, 2017)
Working within a Foucauldian approach to governmentality and the ethics of self-care, this article analyzes the implications of the values upheld for caring and governing oneself in the HIV advice column of Criselda Sambeso Dudumashe, publicly HIV-positive herself. The analysis reveals that the central thrust of the advice advances the principle of investing in oneself and taking responsibility for one’s physical and psychological health. Careful self-evaluation for self-improvement, however, means expending time and energy monitoring viral load, CD4 count and physical health. Likewise, monitoring one’s adherence to HIV therapy requires careful evaluation of one’s psychological state, including personal anxieties and fears, as well as the willingness to pursue qualified assistance from experts. Such self-government, it is argued, conjures up a subjective formation whose own discretion on how to gain control of HIV is oriented toward engaging with the best scientific practices and expert advice for its consolidation. In view of the emerging role played by similar platforms on and off line, an exploration of how the self is set in relation to itself, and how self-improvement is governed, offers insight into the contours of subjectivity in the post-AIDS era of treatment possibility.